2021
DOI: 10.1007/s11423-021-10033-4
|View full text |Cite
|
Sign up to set email alerts
|

The IT2 Survey: contextual knowledge (XK) influences on teacher candidates’ intention to integrate technology

Abstract: Prior to this study, a testable model for the influence of contextual knowledge (XK) on teacher candidates’ intention to integrate technology into classroom instruction had not been established. We applied the Decomposed Theory of Planned Behavior (DTPB) to aid us in this effort. Our work (a) provided a theoretical conceptualization for factors of XK through application of the DTPB, (b) represented the synergistic effects among these factors, and (c) allowed us to explore their influences on teacher candidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A survey is a method used to gather information regarding people's knowledge, attitudes, and behaviors. It enables the collection of data to describe, compare, or explain various aspects of human behavior (Foulger et al, 2021;Geldsetzer, 2020). The research was conducted for teachers in teaching Biology.…”
Section: Methodsmentioning
confidence: 99%
“…A survey is a method used to gather information regarding people's knowledge, attitudes, and behaviors. It enables the collection of data to describe, compare, or explain various aspects of human behavior (Foulger et al, 2021;Geldsetzer, 2020). The research was conducted for teachers in teaching Biology.…”
Section: Methodsmentioning
confidence: 99%
“…2 Application of specific knowledge of Science, Technology, Engineering, Arts, and Mathematics (KAMINSKI ET.AL., 2019). 3 Process of generating ideas in a multidisciplinary group with a focus on problem-solving [5].…”
Section: Description Of Publications Foundmentioning
confidence: 99%
“…Finally, they reported that traditional teaching methods had lost attention and wanted novelties that they could use when they became teachers. Foulger et al [5] present a form called IT2 (Teach with Technology) Survey. They demonstrate the tool as an effective instrument to examine factors associated with contextual knowledge and their influence on technology integration.…”
Section: Description Of Publications Foundmentioning
confidence: 99%
“…Figure 1 (Mishra & Koehler, 2006;Koehler & Mishra, 2009). Notably, a study on technology-infused coursework revealed that the infused approach successfully nurtured teacher candidates' TPACK development, and that infused learning experiences also instilled in candidates a forward-looking perspective and an interest in integrating technology into their future classrooms (Foulger et al, 2021). Preparation programs that adopt an infusion model should recognize that effective implementation of a program-wide effort to address technology content will require teacher education instructors and PK-12 mentor teachers involved have the knowledge and skills (Foulger et al, 2017) to actively contribute to fostering candidates' TPACK and help candidates establish teaching with technology as an ongoing professional growth opportunity.…”
mentioning
confidence: 99%